Hegel, Marxismo y Epistemología - Ayala Saavedra, Roberto (2008)
This article discusses the mutual influence between Hegel and Max, particularly in what has to do with the modern debate of the epistemological issue. The hegelian thought, thanks to the marxist recognition as one of its sources, becomes one of the most important and fundamental contributions to the method of the social and historical sciences. From the negative totality to the theory of combined and unequal development, through the theories of complexity and caos, the dialectic perspective revels itself in the center of the present scientific knowledge.